Scientific Cognitive Achievement Among Track And Field Players And Coaches In Jordan - Aman Khasawneh; Zohair Al Zoubi (My University, 2007)
This study aimed at determining levels of scientific cognitive achievement among track and field players and coaches based on gender and educational level. A descriptive research design was initialized to collect information from a sample of 121 players and coaches. The instrument used in this study had six dimensions including historical, rules, physical, nutrition, injuries and biomechanics. The overall results of the study indicated that track and field players had an average level of scientific cognitive achievement while coaches had above average cognitive achievement. The highest levels of scientific cognitive achievement for both track and field players and coaches were on the rule and historical dimensions where as the lowest levels were on injuries and biomechanics dimensions for track and field players; biomechanics, nutrition and physical dimensions for coaches. Moreover, differences were not found between players and coaches, based on cognitive achievement and gender. However, differences were found based on educational levels for the degree of bachelors. The study proposed a number of theoretical and practical implications for individual working in the aria of track and field.

هدفت هذه الدراسة إلى التعرف على الحصيلة المعرفية العلمية لدى كل من لاعبي ومدربي العاب القوى في الأردن، والتعرف على الفروق في الحصيلة المعرفية العلمية بين لاعبي ومدربي العاب القوى في الأردن، وكذلك التعرف على الفروق في الحصيلة المعرفية العلمية لدى اللاعبين وفقا لمتغيري (الجنس، المؤهل العلمي) وقد تم استخدام المنهج الوصفي لملائمته لطبيعة الدراسة إذا تم اختيار عينة الدراسة من لاعبي ومدربي العاب القوى في الأردن البالغ عددهم (121) وهم يمثلون المجتمع الكلي وقد تم اختيارهم بالأسلوب المسحي. وقد تم استخدام مقياس خاص يتكون من مجموعة أسئلة ذات الاختيار من المتعدد تقيس الحصيلة المعرفية وتم عرضها على الخبراء لمعرفة مدى ملاءمتها لكل بُعد من الأبعاد حيث تم اعتماد الأبعاد الآتية (التاريخي، البدني، التغذية، الإصابات، الميكانيكا الحيوية، القانوني). وقد توصلت الدراسة إلى أن الحصيلة المعرفية كانت ضمن المستوى المتوسط لدى اللاعبين وضمن المستوى فوق المتوسط بقليل لدى المدربين، وكانت أعلى حصيلة معرفية لدى اللاعبين والمدربين في البعد القانوني والتاريخي واقلها في البعد الخاص بالإصابات الرياضية والميكانيكا الحيوية لدى اللاعبين، والبعد الخاص بالميكانيكا الحيوية والبعد الخاص بالتغذية والبعد البدني عند المدربين. كما توصلت الدراسة إلى عدم وجود فروق في الحصيلة المعرفية بين المدربين واللاعبين، وكذلك عدم وجود فروق في الحصيلة المعرفية بين الذكور والإناث، والى تفوق اللاعبين ممن يحملون شهادات البكالوريوس في الحصيلة المعرفية على فئة التوجيهي وأقل. وقد أوصى الباحثان بزيادة الاهتمام بالمدربين واللاعبين وتطوير قدراتهم وزيادة دافعيتهم للتدريب وعقد الدورات والندوات والورش التدريبية والمحاضرات التثقيفية التي تخص المعرفة العلمية في العاب القوى والى إجراء دراسات مشابهة حول دور الاتحادات في تطوير هذه الرياضة.
الحصيلة المعرفية العلمية لدى لاعبي ومدربي العاب القوى في الأردن